2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.24882
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Personal Interactions on the Experience of African American Males on Multiracial Student Teams

Abstract: Virginia Tech and involved with multiple educational research projects with faculty and graduate students. Her research interests include diversity and inclusion, teamwork and communication skills, assessment, and identity construction.Dr. Marie C Paretti, Virginia Tech Marie C. Paretti is an Associate Professor of Engineering Education at Virginia Tech, where she codirects the Virginia Tech Engineering Communications Center (VTECC). Her research focuses on communication in engineering design, interdisciplinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Social networks, such as peers (Dickerson & Zephirin, 2017;Fleming et al, 2013;Litzler & Samuelson, 2013) and mentors Revelo & Baber, 2018), have also been highlighted as essential for the success of Black men in engineering and other students of color. Meaningful engagement of peers through student organizations, such as the National Society of Black Engineers, NSBE (Dickson & Zephirin, 2017;Litzler & Samuelson, 2013) and teams (Cross & Paretti, 2015), are integral to forming a sense of belonging and success. Mentors (Burt et al, 2019;Revelo & Baber, 2018;Slack et al, 2024), especially mentors acquired during undergraduate years, remained sources of motivation as Black men navigated both undergraduate and graduate studies (Burt et al, 2019).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Social networks, such as peers (Dickerson & Zephirin, 2017;Fleming et al, 2013;Litzler & Samuelson, 2013) and mentors Revelo & Baber, 2018), have also been highlighted as essential for the success of Black men in engineering and other students of color. Meaningful engagement of peers through student organizations, such as the National Society of Black Engineers, NSBE (Dickson & Zephirin, 2017;Litzler & Samuelson, 2013) and teams (Cross & Paretti, 2015), are integral to forming a sense of belonging and success. Mentors (Burt et al, 2019;Revelo & Baber, 2018;Slack et al, 2024), especially mentors acquired during undergraduate years, remained sources of motivation as Black men navigated both undergraduate and graduate studies (Burt et al, 2019).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Stereotypes and prejudices have been shown to negatively affect the experience of groups underrepresented in engineering education programs (Fouad et al, 2017;Jackson et al, 2014). The negative impacts include exclusion, loneliness, health problems, and discrimination in team projects (Cech & Rothwell, 2018;Cross & Paretti, 2015;Dee & Gershenson, 2017). For example, encounters with hegemonic masculinity before and during engineering programs negatively affected the experiences of both openly gay and female engineering students (Hughes, 2017).…”
Section: Developing Equitable Teamwork Skillsmentioning
confidence: 99%
“…In a study of African-American male experiences on multiracial student engineering teams, Cross and colleagues found that the social norms of the engineering community decreased African-American students' sense of belonging. 18 Contributing factors included but were not limited to indifferent faculty interactions. The authors recommended that multiracial team projects should be monitored carefully by faculty to ensure positive experiences of all team members.…”
Section: Introductionmentioning
confidence: 99%